The Activities Of Combination Citrus hystrix Peel Extract and Carica papaya Leaves Extract Against Candida albicans and Escherichia coli : Aktivitas Campuran Ekstrak Kulit Citrus hystrix dan Ekstrak Daun Carica papaya Terhadap Candida albicans dan Escherichia coli - Anitasari, Septarini Dian; Sari, Dwi Nur Rikhma (Medicra (Journal of Medical Laboratory Science/Technology), 2021)
Citrus hystrix Peel Extract and Carica papaya Leaves Extract contain several active components that can be used as antimicrobial compounds. The aim was to test a mixture of extracts from Citrus hystrix peel and Carica papaya leaves as growth inhibiting compounds for Candida albicans and Escherichia coli. This study used 4 levels of treatment, namely a combination of papaya leaves extract and orange fruit peel at concentrations of 0%, 25%, 50%, 75% and 100%. The research data were in the form of the diameter of the growth inhibition of Escherichia coli and Candida fungi, which were analyzed using the Kruskall-Wallis test at 5% confidence level and 5% Duncan's test. showed a significant difference between treatments, but the concentration of 100% showed better results to inhibit Escherichia coli (1.58 ± 0.28 d) and the growth of Candida albicans (1.53 ± 0.57b) compared to controls and other concentrations.